Chloride ion-resistant MnO thin-wall hollow sphere catalyst and preparation method thereof

By sintering in an inert gas atmosphere, the MnO thin-walled hollow sphere catalyst was prepared, and the problems of high catalytic temperature, long reaction time and insufficient chloride ion resistance in the prior art were solved, and more efficient CO2 desorption and stable catalytic effects were achieved.

CN119114058APending Publication Date: 2024-12-13SHANGHAI CHINA SHIPBUILDING MATERIALS ENG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411225462.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the solid acid catalyst in the carbon dioxide trap for ships has a high catalytic temperature, a long reaction time, and is not resistant to chloride ions, which affects the efficiency and stability of CO2 desorption.

Method used

Polystyrene spheres are used as templates to sinter the MnO thin-walled hollow sphere catalyst in an inert gas atmosphere to improve the chloride ion resistance and catalytic efficiency of the catalyst.

Benefits of technology

The CO2 desorption temperature and time are reduced, the contact area between the catalyst and the absorbent is increased, the anti-chlorine ion performance of the catalyst is enhanced, and the catalytic activity remains stable after washing in seawater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114058A_ABST
    Figure CN119114058A_ABST
Patent Text Reader

Abstract

The invention discloses a chloride ion-resistant MnO thin-wall hollow sphere catalyst and a preparation method thereof, the catalyst is a multilayer hollow sphere formed by sintering MnO spherical powder, and the outer diameter is 0.2-10 mm; the thickness of the wall is 10-1000 [mu] m; the particle size of the MnO spherical powder is 0.1 to 70 [mu] m. The MnO catalyst is prepared into the thin-wall hollow sphere, the contact area of the catalyst and the absorbent is ensured by utilizing the characteristics of porosity, high specific strength and low density of the hollow sphere, and the catalytic efficiency is improved; mnO is used as a catalyst, so that the catalyst has good chloride ion resistance and can keep normal catalytic activity after being washed with seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal oxide catalysts, and specifically relates to a chloride ion-resistant MnO thin-wall hollow sphere catalyst and a preparation method thereof. Background Art

[0002] In the CO2 capture device for ships, organic amines are used to absorb CO2, and then desorb CO2 (amine catalytic regeneration). At this time, steam heating (about 100-120°C) is required. In order to promote the desorption process and reduce the desorption temperature and time, a catalyst needs to be added to speed up the reaction. 2 The desorption catalyst is a solid acid material. For example, patent document CN1094539801A discloses a method for desorption of CO 2 Fe desorbed from amine solution 2 O 3 / ZrO 2 / SO 4 2- - Preparation method of molecular sieve composite catalytic regeneration material; Patent document CN110681410A discloses a method for preparing a catalytic regeneration material for rich CO 2 Preparation method of SBA-15 molecular sieve-based supported catalytic regeneration material for desorption of amine solution. However, the solid acid catalyst in the above document is in powder form, and only the surface is in contact with the carbon dioxide absorbent, which is inconvenient to use and has a high catalytic temperature and a long reaction time. Patent document CN116747857A discloses a catalytic regeneration material of a carbon capture amine absorbent with a shell-core structure, in which the core is a carbon material and the shell is a metal oxide containing iron, zirconium, manganese, cobalt, nickel and copper. The above research results show that adding solid acid can serve as an acid site to improve CO 2 The desorption efficiency is high. However, the contact area between the catalyst and the amine absorbent is limited and the carbon material occupies most of the weight, so the catalytic effect per unit weight needs to be improved. Moreover, seawater is often used when washing exhaust gas on ships, which requires the catalyst to have good chloride ion resistance, but the chloride ion resistance of the catalysts in the above-mentioned documents cannot meet the requirements.

[0003] As a structural and functional integrated material, metal hollow sphere composites have the characteristics of low density and high porosity. They can be used as reinforcements to prepare composite materials. They have been widely studied in the fields of acoustics, shielding, damping, energy absorption, and heat absorption, and have also entered the fields of biology, chemistry, energy, and environmental protection. As for metal hollow sphere composites as catalysts, some scholars have used in-situ synthesis methods to prepare silicon dioxide-ruthenium-nickel hollow spheres for use as catalysts for the hydrolysis and dehydrogenation of ammonia borane. In addition to its application as a catalyst, metal hollow spheres have already emerged in the application of hydrogen storage composites due to their low density and high specific surface area.

[0004] The preparation methods of metal hollow spheres are generally divided into template removal method and template-free method. In the template removal method, round particles with stable chemical properties under certain conditions are usually used as templates for hollow spheres. A layer of metal or metal oxide powder is wrapped on the template by a certain method to form a blank, and then the template is removed to obtain metal hollow spheres. In the template removal method, polystyrene is often used as a template for metal hollow spheres due to its low price; in the process of preparing metal hollow spheres, the main method used in the template removal stage is vacuum sintering. In vacuum sintering, the sintering temperature and holding time will not only affect the success rate of metal hollow spheres, but also affect the performance of metal hollow spheres, including mechanical properties and catalytic properties. Some researchers also use polystyrene and polyacrylic acid as templates for metal hollow spheres, and finally use chemical reactions to prepare encapsulated silver nanoparticles (Ag@SiO 2 ) hollow silica spheres.

[0005] For example, patent document CN117884142A discloses a hollow spherical composite catalyst Pt / MnO 2 / MnCo 2 O 4 , MnCo 2 O 4 It is a hollow microsphere with a spinel structure composed of manganese and cobalt double transition metal oxides. It is a porous structure composed of a large number of randomly distributed and interconnected nanosheets, with many cavities between adjacent nanosheets. The cavity diameter is 0.9-1μm; MnO 2 The particles are uniformly loaded in the hollow MnCo 2 O 4 The diameter of the microspheres is 95-105nm; the Pt nanoparticles are smaller, with a particle size of 2-20nm, and are evenly loaded on the hollow spherical MnCo 2 O 4 and MnO 2 However, the Pt element used in this document is relatively expensive, and MnO 2 It is directly generated and loaded on MnCo during preparation 2 O 4 The hollow sphere is not suitable for the continuous flushing conditions in the carbon dioxide capture device, and its bonding strength needs to be improved. Summary of the invention

[0006] The present invention aims to provide a chloride ion resistant MnO thin-wall hollow sphere catalyst and a preparation method thereof. The hollow sphere catalyst is prepared by sintering a polystyrene sphere as a template in a circulating inert gas atmosphere to obtain a MnO thin-wall hollow sphere for CO rich 2 Amine solution desorption regeneration of CO 2 , in order to solve the problems existing in the prior art such as high catalytic temperature, long reaction time, and catalyst intolerance to chloride ions.

[0007] In order to achieve the above technical objectives, the technical solution of the present invention is as follows:

[0008] The invention discloses a chloride ion resistant MnO thin-wall hollow sphere catalyst, characterized in that the catalyst is a multilayer hollow sphere sintered from MnO spherical powder, with an outer diameter of 0.2-10 mm, preferably 2-8 mm; a wall thickness of 10-1000 μm, preferably 100-500 μm, and examples thereof include 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, etc.; and a particle size of the MnO spherical powder of 0.1-70 μm, preferably 10-65 μm, and examples thereof include 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, etc.

[0009] The invention discloses a method for preparing a chloride ion resistant MnO thin-wall hollow sphere catalyst. The method comprises the following steps: using polystyrene spheres as inner layer templates, coating MnO spherical powder on the surface of the polystyrene spheres with a binder, and sintering under the protection of an inert gas to remove the polystyrene spheres and the binder, thereby obtaining the MnO thin-wall hollow sphere catalyst.

[0010] More specifically, the preparation method of a chloride ion resistant MnO thin-wall hollow sphere catalyst described in the present invention comprises the following steps: (1) placing polystyrene balls in MnO spherical powder and rolling them, and spraying a binder solution therein at the same time, so that the MnO spherical powder is bonded and coated on the surface of the polystyrene balls; the diameter of the polystyrene balls is 0.1 to 9 mm, preferably 3 to 5 mm; (2) drying after coating to obtain a MnO hollow sphere embryo; (3) placing the MnO hollow sphere embryo in a high-temperature furnace protected by inert gas for sintering, removing the polystyrene balls, and obtaining the chloride ion resistant MnO thin-wall hollow sphere catalyst.

[0011] Preferably, the step (1) is: placing polystyrene balls into an automatic coating machine and adding MnO powder thereto; after turning on the rolling machine, spraying a mist-like binder solution thereto; adjusting the rotation speed of the automatic coating machine and setting the coating time to bond and coat the MnO powder on the surface of the polystyrene balls.

[0012] Preferably, the binder solution is a polyvinyl alcohol aqueous solution with a mass concentration of 4% to 6%, and the amount of the binder solution sprayed is 1 / 10 to 1 / 8 of the mass of the MnO powder.

[0013] Preferably, the rotation speed of the automatic coating machine is 100 to 500 r / min (preferably 100 to 200 r / min), and the coating time is 10 to 20 min.

[0014] Preferably, the drying temperature in step (2) is 10 to 50° C. (preferably 25 to 35° C.), and the drying time is 30 to 120 min.

[0015] Preferably, the inert gas is argon or other gas that does not react with MnO in a high temperature furnace, preferably argon.

[0016] In order to ensure that MnO does not react with other impurity gases (CO 2 , O 2 ) for reaction, in the step (3), the MnO hollow sphere embryo is placed in a high-temperature furnace at room temperature, the high-temperature furnace is filled with argon, the argon is continuously passed and the temperature is started to rise, and the temperature is kept at 300-400°C (preferably 330-360°C, for example 350°C) for 20-50 minutes; the temperature is continued to rise to 900-1350°C and then kept for 1-3 hours, and the MnO thin-walled hollow sphere is obtained after cooling with the furnace. In order to save argon, the argon flow can be turned off above 350°C. More preferably, in the step (3), the temperature is raised to 350-400°C at 1-5°C / min and kept for 20-50 minutes; in order to ensure that the polystyrene beads are completely decomposed, the temperature is raised to 930-1100°C at 10-20°C / min (preferably 15°C / min) and kept for 1-3 hours.

[0017] The chloride ion-resistant MnO thin-wall hollow sphere catalyst of the present invention is used for CO-rich 2 Amine solution desorption regeneration of CO 2 .

[0018] Compared with the prior art, the present invention has the following characteristics:

[0019] The invention prepares MnO hollow sphere embryos by an automatic coating method, has the characteristics of low manufacturing cost and strong operability, has certain designability, and can realize mass production; in order to ensure the purity of MnO during the sintering process, argon gas is passed throughout the sintering process and the furnace cooling process at a temperature below 350° C.; the MnO catalyst is made into a thin-walled hollow sphere, and the porous, high specific strength and low density characteristics of the hollow sphere are utilized to ensure the contact area between the catalyst and the absorbent, thereby improving the catalytic efficiency; and MnO is used as a catalyst, has good chloride ion resistance, and can maintain normal catalytic activity after seawater washing. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an electron microscope image of the MnO spherical powder of the present invention stacked on the surface of a polystyrene ball.

[0021] Figure 2 This is a metallographic photograph of the sphere wall of the MnO thin-wall hollow sphere catalyst of the present invention.

[0022] Figure 3 The macroscopic surface morphology of the MnO thin-wall hollow sphere catalyst of the present invention is shown in FIG. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0024] Those skilled in the art should recognize that the present embodiment is only used to illustrate the present invention, and is not used to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.

[0025] Example 1

[0026] A method for preparing a chloride ion-resistant MnO thin-wall hollow sphere catalyst comprises the following steps:

[0027] S1, putting polystyrene balls with an average diameter of 3 mm into the rolling device of the automatic coating machine, adding MnO spherical powder with an average particle size of 45 μm thereto; turning on the rolling device; adjusting the rotation speed of the rolling device to 150 r / min; using a polyvinyl alcohol aqueous solution with a concentration of 6% as a binder, and the amount of the binder is 1 / 10 of the mass of the MnO spherical powder; at the same time, spraying the atomized binder solution into the rolling device through a nozzle device, and the coating time is 12 minutes; after the coating is completed, taking out the blank, and naturally drying it at a room temperature of 30-35° C., and the drying time is 90 minutes, to obtain a MnO hollow sphere blank;

[0028] S2, put the MnO hollow sphere embryo into a white alumina crucible, and then send it into a high-temperature vacuum furnace at room temperature; introduce argon gas into the high-temperature vacuum furnace, and when it is detected that the outlet is full of argon gas, start heating, and heat to 350℃ at a rate of 1℃ / min, keep warm for 30min, at which time the binder is gasified and volatilized; in order to ensure that the polystyrene beads are completely decomposed, heat to 930℃ at a rate of 15℃ / min, keep warm for 2h, at which time the MnO spherical powder is formed by metallurgy, cooled with the furnace, and a MnO thin-walled hollow sphere catalyst is obtained. After testing, the outer diameter of the MnO thin-walled hollow sphere catalyst is 4-8mm, and the wall thickness is 250-300μm.

[0029] Example 2

[0030] A method for preparing a chloride ion-resistant MnO thin-wall hollow sphere catalyst comprises the following steps:

[0031] S1, putting polystyrene balls with an average diameter of 4 mm into the rolling device of the automatic coating machine, adding MnO spherical powder with an average particle size of 65 μm thereto; turning on the rolling device; adjusting the rotation speed of the rolling device to 200 r / min; using a 5% polyvinyl alcohol aqueous solution as a binder, and the amount of the binder is 1 / 9 of the mass of the MnO spherical powder; at the same time, spraying the atomized binder solution into the rolling device through a nozzle device, and the coating time is 15 minutes; after the coating is completed, taking out the blank, and naturally drying it at room temperature of 30-35° C., and the drying time is 90 minutes, to obtain a MnO hollow sphere blank;

[0032] S2, put the MnO hollow sphere embryo into a white alumina crucible, and then send it into a high-temperature vacuum furnace at room temperature; introduce argon gas into the high-temperature vacuum furnace, and when it is detected that the outlet is full of argon gas, start heating, and heat to 360℃ at a rate of 2℃ / min, and keep it warm for 30min, at which time the binder is gasified and volatilized; in order to ensure that the polystyrene beads are completely decomposed, heat to 1000℃ at 17℃ / min, and keep it warm for 2h, at which time the MnO spherical powder is formed by metallurgy, cooled with the furnace, and a MnO thin-walled hollow sphere catalyst is obtained. After testing, the outer diameter of the MnO thin-walled hollow sphere catalyst is 3-5mm, and the wall thickness is 250-300μm.

[0033] Example 3

[0034] A method for preparing a chloride ion-resistant MnO thin-wall hollow sphere catalyst comprises the following steps:

[0035] S1, putting polystyrene balls with an average diameter of 5 mm into a rolling device of an automatic coating machine, adding MnO spherical powder with an average particle size of 30 μm thereto; turning on the rolling device; adjusting the rotation speed of the rolling device to 100 r / min; using a 5% polyvinyl alcohol aqueous solution as a binder, and the amount of the binder is 1 / 8 of the mass of the MnO spherical powder; at the same time, spraying the atomized binder solution into the rolling device through a nozzle device, and the coating time is 20 minutes; after the coating is completed, taking out the blank, and naturally drying it at a room temperature of 30 to 35° C., and the drying time is 100 minutes, to obtain a MnO hollow sphere blank;

[0036] S2, put the MnO hollow sphere embryo into a white alumina crucible, and then send it into a high-temperature vacuum furnace at room temperature; introduce argon gas into the high-temperature vacuum furnace, and when it is detected that the outlet is full of argon gas, start heating, and heat to 350℃ at a rate of 1℃ / min, keep warm for 45min, at which time the binder is gasified and volatilized; in order to ensure that the polystyrene beads are completely decomposed, heat to 1200℃ at 15℃ / min, keep warm for 2h, at which time the MnO spherical powder is formed by metallurgy, cooled with the furnace, and a MnO thin-walled hollow sphere catalyst is obtained. After testing, the outer diameter of the MnO thin-walled hollow sphere catalyst is 2-4mm, and the wall thickness is 300-350μm.

[0037] Test experiment example

[0038] Using 30% ethanolamine aqueous solution as the absorption liquid, absorbing saturated CO 2 Then desorb CO 2 (Amine catalytic regeneration), CO was tested without adding catalyst, only adding MnO spherical powder catalyst and MnO thin-walled hollow sphere catalyst of Example 1-3. 2 The desorption effect of the catalyst was tested after immersion in 3.5wt% NaCl for 14 days. 2 The desorption effect, desorption temperature and complete desorption time are listed in Table 1.

[0039] Table 1 Comparison of amine catalytic regeneration effects

[0040]

[0041] As can be seen from Table 1, the MnO thin-walled hollow sphere catalyst of the present invention is used for CO-rich 2 Amine solution desorption regeneration of CO 2 It has obvious advantages, not only can reduce CO 2 The desorption temperature can also be greatly shortened. Even if the MnO thin-walled hollow sphere catalyst of the present invention is immersed in 3.5wt% NaCl for 14 days, its catalytic effect is only slightly reduced, which is still much higher than that of MnO spherical powder. When MnO spherical powder is used as a catalyst, CO 2 The desorption temperature is lower than that of the catalyst-free state, and the complete desorption time is only slightly lower than that of the catalyst-free state.

Claims

1. A chloride ion resistant MnO thin-wall hollow sphere catalyst, characterized in that: The catalyst is a multi-layer hollow ball sintered from MnO spherical powder, with an outer diameter of 0.2-10 mm and a wall thickness of 10-1000 μm. The particle size of the MnO spherical powder is 0.1-70 μm.

2. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 1, characterized in that: The outer diameter of the multilayer hollow sphere is 2-8 mm, and the wall thickness is 100-500 μm.

3. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 1, characterized in that: The particle size of the MnO spherical powder is 10 to 65 μm.

4. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to any one of claims 1 to 3, characterized in that: The polystyrene spheres are used as inner layer templates, and MnO spherical powder is coated on the surface of the polystyrene spheres by using a binder; the polystyrene spheres and the binder are removed by sintering under the protection of an inert gas, thereby obtaining a MnO thin-wall hollow sphere catalyst.

5. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 4, characterized in that: The method comprises the following steps: (1) placing polystyrene balls in MnO spherical powder and rolling them, and spraying a binder solution therein at the same time, so that the MnO spherical powder is bonded and coated on the surface of the polystyrene balls; the diameter of the polystyrene balls is 0.1 to 9 mm; (2) drying after coating to obtain a MnO hollow spherical embryo; (3) placing the MnO hollow spherical embryo in a high-temperature furnace protected by inert gas for sintering, removing the polystyrene balls, and obtaining the chloride ion-resistant MnO thin-wall hollow spherical catalyst.

6. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: The diameter of the polystyrene beads is 3 to 5 mm.

7. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: The step (1) is: placing polystyrene balls into an automatic coating machine and adding MnO powder thereto; after turning on the rolling machine, spraying a mist-like adhesive solution thereto; adjusting the rotation speed of the automatic coating machine and setting the coating time to bond and coat the MnO powder on the surface of the polystyrene balls.

8. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: The binder solution is a polyvinyl alcohol aqueous solution with a mass concentration of 4% to 6%, and the amount of the binder solution sprayed is 1 / 10 to 1 / 8 of the mass of the MnO powder.

9. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: The rotation speed of the automatic coating machine is 100-500 r / min, and the coating time is 10-20 min.

10. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: The drying temperature in step (2) is 10 to 50° C., and the drying time is 30 to 120 minutes.

11. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: The inert gas is argon or other gases that do not react with MnO in the high temperature furnace.

12. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 5, characterized in that: In the step (3), the MnO hollow sphere embryo is placed in a high-temperature furnace at room temperature, the high-temperature furnace is filled with argon, the argon is continuously passed and the temperature is started to be increased, and the temperature is kept at 300-400° C. for 20-50 minutes; the temperature is further increased to 900-1350° C. and then kept for 1-3 hours, and the MnO thin-walled hollow sphere is obtained after cooling in the furnace.

13. The method for preparing the chloride ion resistant MnO thin-wall hollow sphere catalyst according to claim 12, characterized in that: Raise the temperature to 350-400°C at 1-5°C / min and keep warm for 20-50min; then raise the temperature to 930-1100°C at 10-20°C / min and keep warm for 1-3h.

14. Use of the chloride ion resistant MnO thin-wall hollow sphere catalyst according to any one of claims 1 to 3, characterized in that: Used for desorption of CO2-rich amine solution to regenerate CO2.